LGBT: An evaluation of shariah provisions and the laws of Malaysia and Nigeria - Ali Mohamed, Ashgar Ali; Amuda, Yusuff Jelili (Universiti Sultan Azlan Shah, Malaysia, 2018)
Lesbian, gay, bisexual and transgender (LGBT) is prohibited by the major religions in the world as it is not only a sheer violation of marriage institution but also disrespect for human being as it contradicts the very nature of man’s creation. The mental, emotional and physical completion of the human race is generally achieved through the combination of a male and a female. LGBT however is based on a refutation of this obvious fact, and goes against the laws of procreation. While some countries have legalised LGBT many still consider it abnormal, irrational, unethical and unacceptable to their religious principles, culture and tradition. LGBT is totally against the Malaysian and Nigerian culture, tradition, belief, faith and religion. Malaysia has taken strict measure not to allow LGBT although some have contended that the prohibition of it infringes basic principles of human rights. It is also a punishable crime both under syariah law. Having said the above, this paper therefore discusses the ethical and legal issues surrounding the LGBT and the Islamic viewpoint on the LGBT sexual activities. The social effect of LGBT to the institution of marriage is also discussed. Throughout the discussion and analysis, the qualitative and quantitative methods were applied. The test samples and data are taken from selected Malaysia and Nigeria respectfully. In the end, useful suggestion and solutions were suggested on the LGBT in the interest of society at large.